Conflict Management in the School Environment: Mediation Appoach to Improve Organisational Climate - Ahmad Irwan Ardiansyah Irwan; Eka Diana (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is driven by the dynamics of conflict in the school environment, which, if not managed properly, can damage the quality of working relationships, hinder organisational coordination, and weaken the organisational climate in educational institutions. This study aims to analyse conflict management thru a mediation approach to improve the organisational climate. This research uses a qualitative, case-study approach. The research location was chosen because MA Nurul Jadid is an educational institution with distinctive organisational characteristics within a pesantren environment, as well as dynamics in the relationships between leaders, teachers, educational staff, and students that have the potential to cause organisational conflicts. Data collection techniques include observation, in-depth interviews, and documentation. The research informants are five individuals: the head of the madrasah, the deputy head of the madrasah responsible for the curriculum, a teacher, an educational staff member, and a student. Data were analysed using the interactive model of Miles, Huberman, and Saldaña thru the stages of data reduction, data presentation, and conclusion drawing. The research results show that conflicts generally arise from differences in perception, misunderstandings, discrepancies in task execution, and differences in communication styles among school members. The conflict was managed thru a mediation approach that emphasised dialog, deliberation, clarification, and joint problem-solving. The implementation of mediation has proven capable of maintaining harmonious working relationships, enhancing communication openness, encouraging mutual respect, and creating a more conducive work atmosphere.